Metal contamination of food : - Reilly, Conor (Blackwell Science, 2002)
Reilly (emeritus, public health, Queensland U. of Technology, Australia) summarizes the available information on metal contamination of foods and on their health implications. The material primarily focuses on known data from scientific analytical procedures, although there is some discussion of historical and legal aspects. After describing the basic science of the field, he presents chapters focusing on individual metals, offering information on contaminant vectors, chemical and physical properties, and human toxicity